Combined effects of agrochemical contamination and forest loss on anuran diversity in agroecosystems of east-central Argentina - Suarez, Romina Paula (2020)
Agricultural expansion and intensification has led globally to a rapid landscape structure change and high agrochemical use resulting in habitat loss and degraded environmental quality. Co-occurrence of landscape change and agrochemical contamination threatens biodiversity and might have interactive effects especially for organisms with complex life-cycles such as amphibians. We evaluated effects of landscape structure and agrochemical contamination at different spatial scales on anurans in Entre Rios, Argentina. We selected 35 independent stream headwaters along an agricultural expansion and intensification gradient. We conducted anuran call surveys from spring 2012 to summer 2013 and obtained detection-non detection data to estimate mean richness and focal species occupancy. We quantified forest area and riparian forest width at two spatial scales (sub-basin and local reach scale). We measured nutrients and pesticides in water and sediment. We evaluated anuran response to landscape and contamination variables using GLMs for richness and single season single-species occupancy models for focal species. Anuran diversity increased with forest area and riparian forest width, and decreased at sites with herbicide and nutrient contamination, particularly glyphosate; 2,4-D and nitrates. Also, most focal frog species responded mainly to basin forest and 2,4-D. Negative effects of agrochemical contamination on anuran diversity was mitigated in areas with larger basin forest cover. Agricultural management should ensure the reduction of herbicide and fertilizer use, the sparing of adequate forested habitat within drainage areas, and preservation of riparian forests around anuran breeding habitat to reduce and mitigate the negative effects of agrochemical contamination on anurans diversity in agroecosystems.